Investigation of Antioxidative and Anticancer Potentials of Streptomyces sp. MUM256 Isolated from Malaysia Mangrove Soil - Tan, Loh Teng-Hern; Ser, Hooi-Leng; Yin, Wai-Fong; Chan, Kok-Gan; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Microbiology, 2015)
A Streptomyces strain, MUM256 was isolated from Tanjung Lumpur mangrove soil in Malaysia. Characterization of the strain showed that it has properties consistent with those of the members of the genus Streptomyces. In order to explore the potential bioactivities, extract of the fermented broth culture of MUM256 was prepared with organic solvent extraction method. DPPH and SOD activity were utilized to examine the antioxidant capacity and the results have revealed the potency of MUM256 in superoxide anion scavenging activity in dose-dependent manner. The cytotoxicity of MUM256 extract was determined using cell viability assay against 8 different panels of human cancer cell lines. Among all the tested cancer cells, HCT116 was the most sensitive toward the extract treatment. At the highest concentration of tested extract, the result showed 2.3, 2.0 and 1.8 folds higher inhibitory effect against HCT116, HT29 and Caco-2 respectively when compared to normal cell line. This result has demonstrated that MUM256 extract was selectively cytotoxic towards colon cancer cell lines. In order to determine the constituents responsible for its bioactivities, the extract was then subjected to chemical analysis using GC-MS. The analysis resulted in the identification of chemical constituents including phenolic and pyrrolopyrazine compounds which may responsible for antioxidant and anticancer activities observed. Based on the findings of this study, the presence of bioactive constituents in MUM256 extract could be a potential source for the development of antioxidative and chemopreventive agents.